Stretchable and Shape-Transformable Organohydrogel with Gallium Mesh Frame - Mincheol Lee; Youngjin Choi; Young Min Bae; Seonghyeon Nam; Kiyoung Shin (Gels)
Shape-memory materials are widely utilized in biomedical devices and tissue engineering, particularly for their ability to undergo predefined shape changes in response to external stimuli. In this study, a shape-transformable organohydrogel was developed by incorporating a gallium mesh into a polyacrylamide/alginate/glycerol matrix. The gallium mesh, which transitions between solid and liquid states at moderate temperatures (~29.8 °C), enhanced the hydrogel’s mechanical properties and enabled shape-memory functionality. The composite organohydrogel exhibited a high elastic modulus of ~900 kPa in the solid gallium state and ~30 kPa in the liquid gallium state, enabling reversible deformation and structural stability. Glycerol improved the hydrogel’s moisture retention, maintaining stretchability and repeated heating and cooling cycles. After multiple cycles of the shape-changing process, the organohydrogel retained its mechanical integrity, achieving shape-fixation and recovery ratios of ~96% and 95%, respectively. This combination of shape-memory functionality, stretchability, and mechanical stability makes this organohydrogel highly suitable for applications in flexible electronics, soft robotics, and biomedical devices, where adaptability and shape retention are essential.